3-Wavelength (UV, Blue, Red) Controlled Photo-Confinement for 3D-Printing: Kinetics and Modeling - Jui-Teng Lin; Hsia-Wei Liu; Yin-Chen Chiu; Kuo-Ti Chen; Da-Chuan Cheng (IEEE Access, 2020)
Detailed kinetics for a 3-wavelength photopolymerization confinement (PC) system is presented for both numerical solutions and analytic formulas. The dynamic profiles of oxygen, free radicals, and monomer conversion for various situations of: blue-light only, 2-light (red and UV), and 3-light (red, blue, UV) are obtained. Higher oxygen concentration leads to a lower conversion, which could be enhanced by reducing the S-inhibition via a red or blue light pre-irradiation. We found that pre-irradiation time is given by TP = 200 s for red-light only, and reduced to 150 s, for both red and blue-light. The system under UV-only leads to a conversion lower than that of blue-only. However, conversion could be improved by the dual-light (blue and UV), and further enhanced by the pre-irradiation of red-light. The two competing factors, N-inhibition and S-inhibition, could be independently and selectively tailored to achieve: (i) high conversion of blue-light (without UV-light), enhanced by red-light pre-irradiation for minimal S-inhibition; and (ii) efficient PC initiated by UV-light produced N-inhibition for reduced confinement thickness and for high print speed.